High‐Throughput Production of Cheap Mineral‐Based Heterostructures for High Power Sodium Ion Capacitors. (27th January 2022) - Xiao, Xuhuan; Duan, Xuegang; Song, Zirui; Deng, Xinglan; Deng, Wentao; Hou, Hongshuai; Zheng, Renji; Zou, Guoqiang; Ji, Xiaobo
Abstract: The high‐throughput scalable production of inexpensive and efficient electrode materials at high current densities demanded by industry is a huge challenge for large‐scale implementation of energy storage technologies. Here, inspired by theoretical calculations that a FeS2 /TiO2 heterostructure with built‐in electric field (BEF) can reduce the reaction energy barrier and enhance charge transport, the scalable production of cheap FeS2 /TiO2 heterostructure is fabricated by utilizing natural ilmenite as precursor, exhibiting excellent electrochemical performances for sodium‐ion capacitors (SICs) anode. Assembling it with activated carbon (AC) cathode for SICs delivers high energy density (73.7 Wh kg −1 ) and high power density (10 kW kg −1 ) as well as outstanding cycle lifespan. Impressively, the method breaks through the traditional preparation approach by using natural minerals instead of high‐purity chemical raw materials as precursors for constructing heterojunctions, and price of the mineral is nearly five orders of magnitude lower than that of commercial chemical raw materials with high‐purity, which greatly reduces raw materials cost and is available for mass production. Similarly, the method can be extended to utilize other minerals to construct heterostructures, thus achieving expanded electrochemical performance, which exhibits huge potentials in electrochemical energy storage. Abstract : Abundant natural ilmenite resources are used to fabricate the heterojunction by simple sulfidation treatment. This method greatly decreases the cost of raw materials, which is applicable for high‐throughput production. It has extremely enhanced electrochemical performance due to the effect of the heterojunction interface, which allows the assembled sodium‐ion capacitors to deliver high‐energy density and high‐power density.